2020
DOI: 10.1371/journal.pone.0236083
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a gamification and flipped-classroom program used in teacher training: Perception of learning and outcome

Abstract: Recent years have witnessed the arrival of new methodological horizons in teacher training. Technological resources and mobile connections play a major role in these studies. At the same time, there is a focus on play to increase commitment and motivation. It is in this context that gamification and flipped-classroom strategies have arisen. This paper presents the results of a training program with future Primary Education teachers using gamification and flipped-classroom strategies and techniques. The aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 72 publications
7
24
1
1
Order By: Relevance
“…However, despite the students' positive opinions, their impressions are not as optimistic as in other similar prepandemic studies conducted in the same context. The results in research conducted a year earlier (Gómez-Carrasco et al, 2020), in which students expressed more significant positive views on their self-perceived motivation, one point higher on average, may demonstrate that the consequences of pandemic-related restrictions are causing some unease among university students.…”
Section: Discussionmentioning
confidence: 89%
“…However, despite the students' positive opinions, their impressions are not as optimistic as in other similar prepandemic studies conducted in the same context. The results in research conducted a year earlier (Gómez-Carrasco et al, 2020), in which students expressed more significant positive views on their self-perceived motivation, one point higher on average, may demonstrate that the consequences of pandemic-related restrictions are causing some unease among university students.…”
Section: Discussionmentioning
confidence: 89%
“…As Table 6 reveals, there is a significant correlation, as well, between all items (subscales) when analyzing Pearson's correlation as all the subscales rated −1 > 0 > 1. According to other studies in Social Sciences Education, such as Gómez et al [33], the items corresponding to a traditional conception of heritage (items 4 and 5, monuments, castles, works of art, etc.) have a positive Pearson correlation (0.54 and 0.26) reaching a better rate among Primary trainee teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The research procedure follows a methodological analysis of trainee teachers' conceptions that has already been proven effective in previous studies [32,33]. This analysis was carried out through quantitative data (items 3-19) using the statistics software package IBM SPSS v.24 for Windows.…”
Section: Validation and Analysis Proceduresmentioning
confidence: 99%
“…In this sense, the scientific community that has developed studies on both training methodologies has revealed how these training methods, from their idiosyncrasy and their way of imparting and working on the contents, have turned out to be successful and influential in improving learning. An improvement occurs in different academic processes and factors, such as attitudinal, psychosocial, and student performance ( Gómez-Carrasco et al., 2020 ; Parra-Gonzalez et al., 2020 ).…”
Section: Study Objective and Research Questionsmentioning
confidence: 99%